(untitled) (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
This study investigated the effect of written summary of short stories on EFL learners’ writing skill. To achieve this purpose, the study was conducted through pre-test and post-test design. Thus, a language proficiency test was administered to 150 students and then ninety language learners were selected and assigned to two experimental groups including low and high achievers based on the median score which divided them into two experimental groups. They were instructed to use the cognitive strategy of summary writing after reading the short stories for a whole academic fall semester, 2012. At the end of the treatment period, statistical analyses were conducted through Paired Samples t-test. Results revealed the positive effect of written summary of short stories on both groups developing their writing skill at the pre-intermediate level while the high achievers outperformed the low achievers (p<0.05).